Development of trace metals concentration model for river: application of principal component analysis and artificial neural network - Shazlyn Milleana Shaharudin (Tanjung Malim, 2023)
Development of trace metals concentration model for river: application of principal component analysis and artificial neural network by Shazlyn Milleana Shaharudin